A COMPARATIVE STUDY OF THE RHETORICAL FUNCTIONS AND FEATURES OF PERSONAL PRONOUNS IN ENGLISH AND CHINESE LEGAL NEWS - ZHANG, Qing (Comparative Legilinguistics, 2021)
This paper mainly discusses the distribution and rhetorical functions of personal pronouns in English and Chinese legal news reports. Through the comparative analysis of some English and Chinese legal news texts, this paper finds the following points: English and Chinese legal news generally have two narrative types: objective narrative and semi-dialogic narrative. The differences in narrative type directly affect the distribution of personal pronouns. In objective narrative, the use of third person pronouns accounts for an absolute proportion, and the frequency of using first person and second person pronouns is close to zero. In semi-dialogic narrative, the use of third person pronouns is still the highest, but only slightly higher than the use of first person and second person pronouns, accounting for only a small number. After analysis, this paper holds that there are three reasons for the uneven distribution: first, the differences between the dialogic style and the narrative style; second, the legal narrative being a story narrative; third, the specific restrictions on the use of legal rhetoric.